National Malaria Strategy: Paradigm Shift from Control to Elimination in Bangladesh (Anwer Khan Modern Medical College Journal, 2015)
Abstract not availableAnwer Khan Modern Medical College Journal Vol. 6, No. 1: January 2015, Pages 4